2014
DOI: 10.1371/journal.pone.0108786
|View full text |Cite
|
Sign up to set email alerts
|

Case Based Measles Surveillance in Pune: Evidence to Guide Current and Future Measles Control and Elimination Efforts in India

Abstract: BackgroundAccording to WHO estimates, 35% of global measles deaths in 2011 occurred in India. In 2013, India committed to a goal of measles elimination by 2020. Laboratory supported case based measles surveillance is an essential component of measles elimination strategies. Results from a case-based measles surveillance system in Pune district (November 2009 through December 2011) are reported here with wider implications for measles elimination efforts in India.MethodsStandard protocols were followed for case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Until 2008, India was the only nation among the 193 member nations of the World Health Organization (WHO) to make provision for only a single dose of measles vaccine in their national immunization schedule, whereas all other nations opted for two doses of measles vaccine ( 22 ). In fact, in case-based measles surveillance in Pune, it was observed that, in approximately 40% of confirmed measles cases, the patient acquired the disease despite being immunized with one dose of measles vaccine; thus a single dose of measles vaccine was insufficient to protect the general population ( 23 ). Eventually, in response to the recommendations made by the Indian National Technical Advisory Group on Immunization and the findings of other studies, the government of India introduced a recommendation for a second dose of measles in late 2010 for all children between 16 and 24 months of age ( 12 , 24 , 25 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Until 2008, India was the only nation among the 193 member nations of the World Health Organization (WHO) to make provision for only a single dose of measles vaccine in their national immunization schedule, whereas all other nations opted for two doses of measles vaccine ( 22 ). In fact, in case-based measles surveillance in Pune, it was observed that, in approximately 40% of confirmed measles cases, the patient acquired the disease despite being immunized with one dose of measles vaccine; thus a single dose of measles vaccine was insufficient to protect the general population ( 23 ). Eventually, in response to the recommendations made by the Indian National Technical Advisory Group on Immunization and the findings of other studies, the government of India introduced a recommendation for a second dose of measles in late 2010 for all children between 16 and 24 months of age ( 12 , 24 , 25 ).…”
mentioning
confidence: 99%
“…In addition, sensitizing health professionals to the need to conduct measles outbreak-based surveillance in all of the states and union territories of India can also assist in reducing the incidence of the disease ( 27 ). Further, crucial evidence can be obtained by undertaking case-based measles surveillance activities across all settings using the standardized guidelines proposed by the Government of India ( 23 , 28 ).…”
mentioning
confidence: 99%
“…This argument is supported by a mathematical model of the impact of antibody level on seroconversion and immunity while estimating measures of protection among vaccinees (percentage of susceptibles, number of reported cases, percentage of lifetime spent susceptible) [10]. The importance of MCV2 coverage has again been highlighted in a recent report from India which demonstrated high measles incidence and frequent outbreaks inspite of above 90% MCV1 coverage [11]. There may be several reasons behind this, ranging from immunological to operational.…”
Section: Commentarymentioning
confidence: 99%
“…Initially aggregate (outbreak-based) surveillance was established in the morbidity and mortality reduction phase, which was later converted into case-based surveillance system supported by a network of high quality laboratories accredited by WHO. [26][27][28] On 13 September 2013 in New Delhi, countries of WHO South-East Asia Region (SEAR) including India committed to eliminate measles and control rubella/congenital rubella syndrome (CRS) by 2020. The resolution was approved during the Sixty-sixth Regional Committee.…”
Section: Introductionmentioning
confidence: 99%